2005
DOI: 10.1080/00343400500213770
|View full text |Cite
|
Sign up to set email alerts
|

Policy Debates Government Output and Expenditure in UK Regions and Sub‐regions: An Analysis of the New Experimental Accounts Data

Abstract: Gripaios P. and Bishop P. (2005) Government output and expenditure in UK regions and sub‐regions: an analysis of the new experimental accounts data, Regional Studies 39 , 805–813. This paper examines the regional and sub‐regional distribution of UK state spending by analysing new data available from recently published Regional Government Accounts. The data indicate wide variations in public spending per head across regions, with London being a particular beneficiary. The results do not indicate any relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This is surprising as there (2003) and Gripaios and Bishop (2005). These studies have revealed wide variations across regions both in terms of "identifiable" public expenditure, for the benefit of a particular population, and "non-identifiable" spending such as that on defence, which is seen, in principle, as benefiting citizens of the UK in total.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is surprising as there (2003) and Gripaios and Bishop (2005). These studies have revealed wide variations across regions both in terms of "identifiable" public expenditure, for the benefit of a particular population, and "non-identifiable" spending such as that on defence, which is seen, in principle, as benefiting citizens of the UK in total.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, spatial disparities in spending inevitably have important economic Gripaios and Bishop (2005)). Whether such a distribution is "fair" is an arguable proposition depending on the extent to which one believes that lottery funding should go on iconic projects, wherever they are most properly located, or, whether it should be skewed towards regions of greater need.…”
Section: Introductionmentioning
confidence: 99%